Alternative Processing Technology for Converting Vegetable Oils and Animal Fats to Clean Fuels and Light Olefins - 田华 李春义 杨朝合 山红红 (Chinese journal of chemical engineering, 2008)
Since the production cost of biodiesel is now the main hurdle limiting their applicability in some areas, catalytic cracking reactions represent an alternative route to utilization of vegetable oils and animal fats. Hence, catalytic transformation of oils and fats was carried out in a laboratory-scale two-stage riser fluid catalytic cracking （TSRFCC） unit in this work. The results show that oils and fats can be used as FCC feed singly or co-feeding with vacuum gas oil （VGO）, which can give high yield （by mass）of liquefied petroleum gas （LPG）, C2-C4 oletms, tor example 45% LPG, 47% C2-C4 olefins, and 77.6% total liquid yield produced with palm oil cracking. Co-feeding with VGO gives a high yield of LPG （39.1%） and propylene （18.1%）. And oxygen element content is very low （about 0.5%） in liquid products, hence, oxygen is removed in the form of H2O, CO and CO2. At the same time, high concentration of aromatics （C7-C9 aromatics predominantly） in the gasoline fraction is obtained after TSRFCC reaction of palm oil, as a result of large amount of hydrogen-transfer, cyclization and aromatization reactions, Additionally, most of properties of produced gasoline and diesel oil fuel meet the requirements of national standards, containing little sulfur. So TSRFCC technology is thought to be an alternative processing technology leading to production of clean fuels and light olefins.